Terapi Montelukast pada Asma - Alfian Nur Rosyid; Arief Bakhtiar; Daniel Maranatha; Muhammad Amin (MEDICINUS, 2024)
Asthma is a chronic inflammatory respiratory condition caused by various inflammatory mediators, including those from the arachidonic acid pathway, which serves as a precursor for leukotrienes and prostaglandins. Leukotriene receptor antagonists (LTRAs) have been approved since 1998 as a treatment for asthma. Montelukast is one of the LTRAs that is useful for asthma control, including cases that accompanied by allergic rhinitis. A daily dose of 5-10 mg is recommended for persistent asthma as the preferred controller. LTRAs are not recommended for acute asthma exacerbation due to their relatively slow onset, but they are beneficial in preventing exacerbations. They are also indicated for exercise-induced asthma (EIA), and can be taken 2 hours prior to exercise. Montelukast can be administered as monotherapy or added to LABA-ICS therapy. It is suitable for adults, children, and infants over 1 year of age, preferably taken at night to prevent symptoms in the early morning. Possible side effects include respiratory tract infections, abdominal pain, diarrhea, and neuropsychiatric disorders. Montelukast is considered safe for use during pregnancy and breastfeeding. Physicians should provide comprehensive education for patients regarding medication compliance and the potential risks of side effects. Regular daily use of montelukast is beneficial in preventing acute exacerbations in asthma patients.